Amorphization and defect engineering in constructing ternary composite Ag/PW10V2/am-TiO2−x for enhanced photocatalytic nitrogen fixation. (5th January 2022) - Feng, Caiting; Wu, Panfeng; Li, Qinlong; Liu, Jiquan; Wang, Danjun; Liu, Bin; Wang, Tianyu; Hu, Huaiming; Xue, Ganglin
Abstract : Ag/PW10 V2 /am-TiO2− x was designed by decorating OVs-enriched am-TiO2− x with Ag NPs and PW10 V2 . The formed Z -scheme heterojunction, Ag–am-TiO2− x interface and plentiful surface OVs account for its high photocatalytic efficiency in nitrogen fixation. Abstract : Photo-driven nitrogen fixation involves the activation and hydrogenation processes of molecular nitrogen in producing ammonia at the photocatalyst surface. Herein, significant enhancement of the catalytic efficiency is achieved via constructing a ternary Ag/PW10 V2 /am-TiO2− x composite (the optimal PW10 V2 and Ag NPs loadings are 14.5 wt% and 1.5 wt%, respectively) with high specific surface area of 513 m 2 g −1 . The well-designed Z -scheme heterojunction between divanadium substituted phosphotungstic acid (PW10 V2 ) and amorphous TiO2− x (am-TiO2− x ) combined with localized surface plasmon resonance (LSPR) of Ag NPs endowed the ternary Ag/PW10 V2 /am-TiO2− x composite with superior oxidation–reduction performance. Accommodated by amorphization and defect engineering, enriched surface oxygen vacancies (OVs) were produced. In the absence of a sacrificial agent, high NH3 /NH4 + productions of 424.9 μmol gcat −1 were achieved under a nitrogen atmosphere when irradiating under simulated sunlight for 2 h. The results show that the enhancement of catalytic efficacy is well correlated with a Z -scheme heterojunction and Ag–am-TiO2− x interface with factors of 1.2–1.4 and 1.4–1.8, respectively. The roles of the surface OVs and amorphous structure are emphasized when compared with anatase TiO2− x and Ag/PW10 V2 /anatase-TiO2− x . In addition to the excellent photocatalytic activity, the composite demonstrates high photochemical stability with negligible activity decay. This work also gives some inspiration to prepare polyoxometalates-based photocatalysts with high activity for photocatalytic nitrogen fixation.